(untitled) (Eurasian Medical Research Periodical, 2022)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease; its detection in the general population has reached global proportions. Although the disease has a relatively mild course in its early stages, the development of non-alcoholic steatohepatitis, cirrhosis and hepatocellular carcinoma during its natural course leads to a worse long-term prognosis. A growing body of evidence suggests that NAFLD has a complex, multifaceted aetiology involving many factors, including genetic factors. In this review we focus on a genetic component of NAFLD, namely the role of PNPLA3 gene polymorphisms in the development and course of the disease as well as its progression states such as nonalcoholic steatohepatitis, cirrhosis and hepatocellular carcinoma.